The hot country - Butler, Robert Olen (Christopher Marlowe Cobb thriller, 2012)
Christopher Marlowe ("Kit") Cobb, an early 20th-century American war correspondent reporting on Mexico's civil war, witnesses the attempted assassination of a priest and the arrival of strange ships bearing German officials.